Antidiabetic Activity of Catechin from Cinnamon (Cinnamomun Burmanii) by Inhibiting Alfa Glucosidase Enzyme - Zaenab, St; Hasyim, Zohrah (Hasanuddin University, 2022)
Diabetes mellitus (DM) is a chronic disease that occurs when the body experiences insulin resistance. One of the treatment for DM is by inhibiting the performance of the -glucosidase enzyme which is located on the smooth wall. Indonesia is famous for having various types of herbal plants that are often used as traditional ingredients, one of which is cinnamon (Cinnamomun burman II) which has compounds such as catechins that are useful as antioxidants. This research method a docking simulation, the ligand was downloaded in the Pubmed database and the androgen receptor macromolecule was downloaded in the Protein Data Bank (PDB), the ligand structure preparation, the test ligand docking simulation and the comparison uses the pymol,pyrx program, and Lipinski test, toxicity test using the PREADMET program. The results of binding affinity for the test compound, namely catechin compounds, obtained a binding affinity of -8.0 kcal/mol, while the comparative test, metformin, obtained a binding affinity of -3.3 kcal/mol and Lipinski qualifies as non-carcinogens but can be mutagens. These results indicate that catechin compounds have greater inhibition on alpha glucosidase receptors that cause type 2 diabetes mellitus compared to metformin compounds.